The Influence of Product Quality and Price on Purchasing Decisions with Consumer Satisfaction Intervening Variables at Caffe Mazio Coffebistro in Pati - Anisa, Yusnia Agnes Selma; Nurhayati, Nurhayati (Economics and Business International Conference Proceeding, 2024)
This study aims to analyze the influence of product quality and price on purchasing decisions with customer satisfaction as an intervening variable at Mazio Coffebistro in Pati. The sample consists of 100 respondents selected using accidental sampling method. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results show that product quality and price have a significant positive effect on customer satisfaction. Price and customer satisfaction have a significant positive effect on purchasing decisions, while product quality does not directly influence purchasing decisions. Customer satisfaction is proven to mediate the relationship between product quality and price on purchasing decisions. These findings highlight the importance of appropriate pricing strategies and product quality improvement to enhance customer satisfaction, which in turn influences purchasing decisions. This research contributes theoretically to the development of marketing science and provides practical implications for cafe business owners in formulating effective marketing strategies.